Tawakkal dan Istiṭā‘ah Kesehatan Jamaah Haji Risiko Tinggi: Kajian Fikih Kedokteran Berbasis Maqāṣid al-Syarī‘ah - Tw, Afrizal; Bantolo, Suryo (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
High-risk Hajj pilgrims often stand at the intersection of spiritual reliance on God and the medical demands of performing the pilgrimage safely. This issue becomes urgent when tawakkal is understood as passive surrender that is not always accompanied by compliance with medical screening, treatment, and healthcare recommendations. Hajj requires adequate physical and mental readiness, particularly for elderly pilgrims and those with chronic diseases who are vulnerable to clinical deterioration during the pilgrimage. This study aims to formulate a concept of tawakkal that is compatible with health-related istithā‘ah through a medical jurisprudence approach grounded in maqāṣid al-syarī‘ah. It employs normative-integrative Islamic legal research using conceptual, maqāṣidī, and medical jurisprudence approaches. The study draws on the Qur’an, hadith, works on Hajj jurisprudence, Islamic legal maxims, maqāṣid studies, and relevant literature on Hajj health. The findings show that tawakkal cannot be separated from medical effort. Health screening, adherence to therapy, control of chronic diseases, acceptance of rukhsah, and decisions to postpone or limit ritual activities under certain conditions are part of realizing hifẓ al-nafs. The article argues that health-related istithā‘ah is not merely an administrative requirement for Hajj departure, but a sharī‘ah-based instrument to ensure that worship is performed without neglecting the protection of life. It offers a reconstruction of tawakkal in Hajj medical jurisprudence so that tawakkal does not fall into religious fatalism, but becomes an ethical foundation for protecting high-risk Hajj pilgrims.